1984
DOI: 10.1111/j.1365-2990.1984.tb00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Amyloid P Component in Cerebro‐vascular Amyloidosis

Abstract: The presence of amyloid P component (AP) in cerebral amyloid deposits was sought using a direct immunoperoxidase technique. AP was detected in the amyloid deposits in the vessel walls but was absent from the intracerebral plaques in tissue from patients with senile cerebral amyloidosis. AP was also present in the amyloid deposits in the vessel walls of patients with the Icelandic form of hereditary cerebral haemorrhage associated with amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 19 publications
(5 reference statements)
4
18
0
Order By: Relevance
“…No immunoreactivity against other known amyloidogenic proteins (amyloid fibril protein AA, 33 K and X light immunoglobulin chains, 34 or prealbumin 3536 ) was detected. As in other types of amyloidosis and consistent with an earlier study 37 the amyloid P component was demonstrated to occur in the amyloid deposits.…”
Section: Figure 3 Examination Of Leptomeningeal Small Arteries Outsisupporting
confidence: 91%
“…No immunoreactivity against other known amyloidogenic proteins (amyloid fibril protein AA, 33 K and X light immunoglobulin chains, 34 or prealbumin 3536 ) was detected. As in other types of amyloidosis and consistent with an earlier study 37 the amyloid P component was demonstrated to occur in the amyloid deposits.…”
Section: Figure 3 Examination Of Leptomeningeal Small Arteries Outsisupporting
confidence: 91%
“…SAP has been found associated in vivo with animal and human amyloid deposits irrespective of the biochemical nature of the amyloid subunit (reviewed in [1]) and colocalizing with neurofibrillary pathology in a various neurodegenerative conditions including Creutzfedt-Jacob disease, Parkinson's and diffuse Lewy body disorders, and in the parkinsonism-dementia complex of Guam [4,[9][10][11]. SAP immunoreactivity is also commonly observed in Down's syndrome, AD, and in amyloid disorders with primarily cerebrovascular compromise such as Hereditary Cerebral Hemorrhage with Amyloidosis, Icelandic-type [12][13][14][15][16]. In AD brains, the widespread SAP immunoreactivity is evident in association with plaques and amyloid-laden vessels as well as with neurofibrillary tangles, but its presence in diffuse pre-amyloid deposits is controversial (reviewed in [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SDS-PAGE analysis of culture medium did not show any appearance of the 8 kDa protein band which would further suggest that AA fibrils were not formed. Other components present in vivo, such as the different common elements found in several types of amyloid deposits (serum amyloid P, heparan sulphate proteoglycan, Apo-E) [30][31][32][33][34][35], may be required for inducing a partial degradation and/or fibril formation. These common elements may be relevant to test in vitro to determine whether they play a role in the initiation phase of fibril formation.…”
Section: Saa Degradation By Macrophage Cell Linesmentioning
confidence: 99%
“…However, when we consider that macrophages from susceptible mice show a slower SAA degradative processing between 24 and 48 h, one can wonder whether a similar intermittent block in SAA degradation occurring in vivo, where co-factors are present, may represent a 'window of opportunity' for the extracellular fibril formation and deposition. In vivo, co-factors such as heparan sulphate proteoglycans, amyloid P component and/or Apolipoprotein-E (Apo-E) could play a role in the initiation or perpetuation of the fibril formation in the presence of SAA [30][31][32][33][34][35].…”
Section: Saa Degradation By Macrophage Cell Linesmentioning
confidence: 99%